Impact of H216 on the DNA Binding and Catalytic Activities of the HIV Restriction Factor APOBEC3G - Harjes, Stefan (American Society for Microbiology, 2013)
APOBEC3G has an important role in human defense against retroviral pathogens, including HIV-1. Its single-stranded DNA cytosine deaminase activity, located in its C-terminal domain (A3Gctd), can mutate viral cDNA and restrict infectivity. We used time-resolved nuclear magnetic resonance (NMR) spectroscopy to determine kinetic parameters of A3Gctd's deamination reactions within a 5′-CCC hot spot sequence. A3Gctd exhibited a 45-fold preference for 5′-CCC substrate over 5′-CCU substrate, which explains why A3G displays almost no processivity within a 5′-CCC motif. In addition, A3Gctd's shortest substrate sequence was found to be a pentanucleotide containing 5′-CCC flanked on both sides by a single nucleotide. A3Gctd as well as full-length A3G showed peak deamination velocities at pH 5.5. We found that H216 is responsible for this pH dependence, suggesting that protonation of H216 could play a key role in substrate binding. Protonation of H216 appeared important for HIV-1 restriction activity as well, since substitutions of H216 resulted in lower restriction in vivo.